Chilean salmon industry company case: splendor and crisis - Oliva, Ismael; Concha, Guillermo; Araya, Magdalena (Estudios de Administración, 2009)
In 1981 we found that Chile had already become the second largest salmon producer in the world, with 245,000 tons per year, being surpassed only by Norway with 420,000 tons per year of production. By the 1990s, the industry’s growth rate was over 10%. This prosperity had a positive impact on both jobs, income, education and infrastructure in the region where the salmon companies were located. The most surprising thing about the case of Chile is that this industry had started from scratch and in just 20 years had reached the preeminent second place of production in the world. However, on September 7, 2007, an event occurred that had a strong impact on the industry with the appearance of the ISA virus and, consequently, on companies. Some companies closed down, others laid off their employees en masse, and absolutely all fell in profitability. It was the first time that salmon companies had faced an event of this magnitude and their main concern was to know what would be its effect on the industry and how to deal with this situation.